2003
DOI: 10.2754/avb200372030365
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification and Characterization of Rabbit Caecal Mucinolytic Bacteria

Abstract: Sirotek K., E. Santos, V. Benda, M. Marounek: Isolation, Identification and Characterization of Rabbit Caecal Mucinolytic Bacteria. Acta Vet. Brno 2003, 72: 365-370.The aim of our study was to isolate, identify and characterize mucinolytic bacteria from the rabbit caecum. Two hundred and thirty mucin-grown colonies from the caecal contents of 7 rabbits were examined microscopically after the Gram staining. Gram-negative irregular rods were the most numerous mucinolytic isolates (34.1%), followed by gram-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Bacteroides, a significant genus in humans and rabbits, seems to have mucinolytic properties (Hill, 1986;Marounek et al, 2000;Sirotek et al, 2003). In humans, B. thetaiotaomicron also has mucinolytic capacity.…”
Section: The Mucosal Layermentioning
confidence: 99%
“…Bacteroides, a significant genus in humans and rabbits, seems to have mucinolytic properties (Hill, 1986;Marounek et al, 2000;Sirotek et al, 2003). In humans, B. thetaiotaomicron also has mucinolytic capacity.…”
Section: The Mucosal Layermentioning
confidence: 99%
“…Some of the most frequent isolated caecal bacteria (Bacteriodes spp.) are the most active genera in mucin digestion (Hill, 1986;Sirotek et al, 2003). Also, Emaldi et al (1979) observed that the main activities of caecal microbiota were in decreasing order: ammonia-user, ureolytic, proteolytic and cellulolytic.…”
Section: The Role Of Nitrogen In Microbial Growthmentioning
confidence: 99%
“…In poultry and pigs, Cambra-López et al (2011a) found a higher proportion of particles from faecal material in PM10 and PM2.5 than in our study. Perhaps the nature of rabbit's hard faeces, which are highly compressed and have a mucin cover (Sirotek et al, 2003), could probably explain such figure 2: Particulate matter airborne samples collected on polycarbonate filters viewed using scanning electron microscopy (600×), from PM2.5 (a), PM10 (b) and TSP (c) samples from fattening rabbit farm. Note: 5 µm diameter filter pores are shown as round dark holes.…”
Section: Discussionmentioning
confidence: 99%